Sexual Disorders: A Behavioral Approach to Their Formation and Therapy - Kocharyan, Garnik (Psychological Counseling and Psychotherapy, 2025)
A behavioural model of sexual disorders is based on the principles of behavioural psychology, according to which these disorders are regarded as a result of acquired forms of behaviour fixed in the process of learning. Undesired or disadaptive sexual patterns (for example, avoidance of intimacy, dependence on certain objects or situations for arousal) can result from negative experience, reinforcement or absence of adequate learning. Behavioural therapy is intended for elimination of learned forms of behaviour (symptoms and syndromes). It is based on the principle, according to which it is possible to get rid of any unhealthy or inadequate manifestation (symptom) with a reflex origin following the same way. Therefore the goal of behavioural therapy consists in destruction of pathological behavioural programmes and formation of normal ones, which are adjusted to reality. The article presents behavioural models of formation of sexual disorders: I. P. Pavlov’s model of classical conditioning (formation of conditioned reflexes); model of operant conditioning (awards: positive and negative reinforcement, punishment); A. Bandura’s model of social learning (the learning takes place when watching behaviour of other people, as well as under the influence of media). The author characterizes determinants of formation of sexual disorders in a behavioural model, gives examples of different sexual dysfunctions and sexual orientation disorders, which develop by behavioural mechanisms. Behavioural interventions used for therapy of sexual disorders are presented, and the author’s behavioural scheme of using medications for treatment of anxious sexual failure expectation syndrome is suggested.